1997
DOI: 10.1007/bf01279566
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of activity and structure of the tonoplast vacuolar-type H+-ATPase in plants with differing CAM expression and in a C3 plant under salt stress

Abstract: Summary. Differences in the activity and structure of the vacuolar H+-ATPase (V-ATPase, EC 3.6.1.3) were investigated in the C3/CAM intermediate plant Kalanchob" blossfeldiana Poellnitz cv. Tom Thumb, with lower or higher expression of CAM, and Hordeum vulgare cv. Carina, grown with or without 150 mM NaC1. In K. blossfeldiana ATP-hydrolysis and H+-transport activity were higher with higher expression of CAM than in plants with very weak CAM. This was mainly due to a larger amount of V-ATPase. Statistical analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0
1

Year Published

2002
2002
2018
2018

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 31 publications
2
6
0
1
Order By: Relevance
“…At least in the case of VHA-B, this appeared to be caused not by an increased amount of SOS2 or VHA-B under salt stress but rather another mechanism that altered binding affinity or stability of the SOS2 interaction with the V-ATPase. This is consistent with other reports showing that the amount of V-ATPase does not change in short-term salt treatments (26,28,46). While it is not known what modification could have altered the binding affinity of SOS2 for the V-ATPase complex, one possibility is posttranslational modification of SOS2 itself.…”
Section: Discussionsupporting
confidence: 82%
“…At least in the case of VHA-B, this appeared to be caused not by an increased amount of SOS2 or VHA-B under salt stress but rather another mechanism that altered binding affinity or stability of the SOS2 interaction with the V-ATPase. This is consistent with other reports showing that the amount of V-ATPase does not change in short-term salt treatments (26,28,46). While it is not known what modification could have altered the binding affinity of SOS2 for the V-ATPase complex, one possibility is posttranslational modification of SOS2 itself.…”
Section: Discussionsupporting
confidence: 82%
“…The vacuolar ç + -ATPase (V-ATPase) manifested much larger changes. The activation of V-ATPase in the vesicles isolated from salt-stressed barley seedlings, at invariable ATP-hydrolase activity, was reported earlier [18,19]. We found that such activation of V-ATPase in the salt-tolerant barley cv.…”
Section: Discussionsupporting
confidence: 72%
“…Such regulation could arise via the modification of c-subunits in the hydrophobic region of V 0 enzyme and the change in the number of these subunits as already established for F 0 F 1 -ATPases [28]. However, in the salt-stressed barley plants, no restructuring was reported in the V 0 domain [18]. Presently we cannot assert which particular mechanism for V-ATPase coupling control is involved in our case.…”
Section: Discussionmentioning
confidence: 68%
“…The fresh weight of different parts of seedlings was measured using analytic balance. At the end of treatment (7 days) the hypocotyls from plants were harvested for the isolation of tonoplast-enriched vesicles (Mariaux et al 1997 modified by Otoch et al 2001). …”
Section: Methodsmentioning
confidence: 99%